Limiting Limited Liability - Guiseppe Dari-Mattiacci (Tinbergen Institute, 2006)
Limited liability may result in inefficient accident prevention, because a relevant portion of the expected harm is externalized on victims. This paper shows that under some restrictive conditions further limiting liability by means of a liability cap can improve caretaking.
Keywords: K13; K32; L59; 330; insolvency; judgment proof; liability; bankruptcy; liability cap